COMPENSATION LIABILITY FOR CONSUMERS OF BEAUTY PRODUCTS THAT DISTRIBUTION LICENSES HAVE BEEN WITHDRAWN BY BPOM PERSPECTIVE COMPILATION OF SHARIA ECONOMIC LAW - Siti Nazar; Mhd. Yadi Harahap (istinbath, 2023)
Cosmetics are defined as particular components designed to be applied to the surface of the human body. Cosmetics are beauty products women use to beautify or change their appearance. It is usually used to beautify the outside of the human body to get an attractive appearance. Even though they are not a basic need, cosmetics are one of the many products used daily and routinely, especially by women. This study aims to find out the form of accountability for compensation related to beauty products whose distribution permits have been withdrawn but whose products are still found circulating in the community and how that will be done according to the views of the Sharia Economic Law Compilation (KHES) and Law No. 8 of 1999 concerning Consumer Protection. This study uses a juridical-normative research method in which legal and statutory theory is the approach. The theory used in this study is the theory of legal protection, namely providing protection for human rights that are harmed by other people. The results of this study explain that legal protection and liability for compensation to consumers, especially for beauty products whose distribution permits have been withdrawn by BPOM, are regulated in KHES and in UUPK Article 4 letter a, which explains the rights of consumers to obtain safety, security and comfort when using goods/services. And business actors are responsible if consumers suffer losses in the future for refunds and provide compensation according to the provisions of Article 19 paragraph (2) for consumers who are harmed to receive compensation for their health.